Electrically Heatable Graphene Aerogels as Nanoparticle Supports in Adsorptive Desulfurization and High‐Pressure CO2 Capture. (9th August 2020) - Xia, Dong; Li, Heng; Mannering, Jamie; Huang, Peng; Zheng, Xiarong; Kulak, Alexander; Baker, Daniel; Iruretagoyena, Diana; Menzel, Robert
Abstract: Reduced‐graphene‐oxide (rGO) aerogels provide highly stabilising, multifunctional, porous supports for hydrotalcite‐derived nanoparticles, such as MgAl‐mixed‐metal‐oxides (MgAl‐MMO), in two commercially important sorption applications. Aerogel‐supported MgAl‐MMO nanoparticles show remarkable enhancements in adsorptive desulfurization performance compared to unsupported nanoparticle powders, including substantial increases in organosulfur uptake capacity (>100% increase), sorption kinetics (>30‐fold), and nanoparticle regeneration stability (>3 times). Enhancements in organosulfur capacity are also observed for aerogel‐supported NiAl‐ and CuAl‐metal‐nanoparticles. Importantly, the electrical conductivity of the rGO aerogel network adds completely new functionality by enabling accurate and stable nanoparticle temperature control via direct electrical heating of the graphitic support. Support‐mediated resistive heating allows for thermal nanoparticle recycling at much faster heating rates (>700 °C∙min −1 ) and substantially reduced energy consumption, compared to conventional, external heating. For the first time, the CO2 adsorption performance of MgAl‐MMO/rGO hybrid aerogels is assessed under elevated‐temperature and high‐CO2 ‐pressure conditions relevant for pre‐combustion carbon capture and hydrogen generation technologies. The total CO2 capacity of the aerogel‐supported MgAl‐MMO nanoparticles is more than double that of the unsupported nanoparticles and reaches 2.36 mmol·CO2 g −1 ads (at p CO2  = 8 bar, T  = 300 °C), outperforming other high‐pressure CO2 adsorbents. Abstract : Supporting hydrotalcite‐derived nanoparticles within graphene‐based aerogels induce remarkable enhancements in adsorptive desulfurization performance (sorption capacity, sorption kinetics, sorbent regenerability), while simultaneously enabling energy‐efficient and extremely fast nanoparticle temperature control via local electrical aerogel heating. The aerogel‐supported nanoparticles also exhibit outstanding CO2 sorption characteristics, especially at high CO2 pressures (1–10 bar), which is important for pre‐combustion capture and hydrogen‐generation technologies.